Pengaruh Self Efficacy, Entrepreneur Orientation, Transformasional Leadership Terhadap Kinerja Nasi Padang - Laurence, Michael; Handayani, Milda; Wijayaningsih, Rini (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the influence of self-efficacy, entrepreneurial orientation, and transformational leadership on the performance of Micro, Small, and Medium Enterprises (MSMEs), particularly Padang rice restaurants in Bekasi City. MSMEs play an important role in the national economy, but they still face challenges in improving their performance sustainably. This study employs a quantitative method, distributing questionnaires to 102 respondents who are operators of Padang rice restaurants, selected through purposive sampling. Data analysis was conducted using multiple linear regression to test the influence of each variable. The results of the study indicate that self-efficacy, entrepreneurial orientation, and transformational leadership have a positive and significant influence on MSME performance, both partially and simultaneously. These findings contribute theoretically and practically to efforts to enhance the competitiveness of traditional culinary-based MSMEs in the era of global competition.